1992
DOI: 10.1212/wnl.42.9.1791
|View full text |Cite
|
Sign up to set email alerts
|

Paralimbic frontal lobe hypometabolism in depression associated with Huntington's disease

Abstract: We measured regional cerebral glucose metabolism using 2-[18F]-fluoro-2-deoxy-D-glucose and positron emission tomography in depressed and nondepressed patients with early Huntington's disease (HD), compared with appropriately matched controls. Caudate, putamen, and cingulate metabolism was significantly lower in patients with HD than in control subjects, independent of mood state. Orbital frontal-inferior prefrontal cortex hypometabolism, however, differentiated depressed patients from both nondepressed patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
1
7

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(97 citation statements)
references
References 0 publications
4
85
1
7
Order By: Relevance
“…Indeed, Bremner et al (1997) found that depressed patients who were 6 weeks into a course of antidepressant treatment exhibited decreases in glucose metabolic rates in the orbitofrontal cortex and thalamus after a tryptophan-depletion-induced acute relapse compared to patients without depressive symptoms. A comparable pattern of abnormality in the orbitofrontal cortical region is seen in refractory depressed patients (Mayberg et al, 1997) and in patients with depression associated with neurological disorders (Bromfield et al, 1992;Mayberg et al, 1990Mayberg et al, , 1992. Mayberg et al (1999) suggested that mood provocation in patients with acute and remitted depression resulted in rCBF decrease in the medial orbitofrontal cortex BA 10/11, which was absent in healthy controls.…”
Section: Orbitofrontal Cortex In Mdd With Bpd Compared To Mddmentioning
confidence: 84%
“…Indeed, Bremner et al (1997) found that depressed patients who were 6 weeks into a course of antidepressant treatment exhibited decreases in glucose metabolic rates in the orbitofrontal cortex and thalamus after a tryptophan-depletion-induced acute relapse compared to patients without depressive symptoms. A comparable pattern of abnormality in the orbitofrontal cortical region is seen in refractory depressed patients (Mayberg et al, 1997) and in patients with depression associated with neurological disorders (Bromfield et al, 1992;Mayberg et al, 1990Mayberg et al, , 1992. Mayberg et al (1999) suggested that mood provocation in patients with acute and remitted depression resulted in rCBF decrease in the medial orbitofrontal cortex BA 10/11, which was absent in healthy controls.…”
Section: Orbitofrontal Cortex In Mdd With Bpd Compared To Mddmentioning
confidence: 84%
“…Anterior cingulate cortex is involved in emotional responses and in sensory, motor, and cognitive processing (Vogt et al, 1992). Positron emission tomographic studies in patients with HD have revealed impairment of activity in the anterior cingulate cortex as well as the striatum (Mayberg et al, 1992). In R6/1 mice, transplantation of wild-type donor cortex to replace diseased anterior cingulate cortex delays the onset of a specific motor symptom of HD (van Dellen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, this cortical area has been demonstrated to exhibit hypometabolism in patients with HD, studied by a variety of noninvasive functional imaging methods (31). Similarly, neuropathological studies have highlighted this area as one exhibiting prominent neurite pathology in this disease (32,33).…”
Section: Discussionmentioning
confidence: 99%